Assessing the therapeutic role of the secretome from mesenchymal stromal cells in genetic models of Parkinson's Disease based on the overexpression of alpha-synuclein - Marques, Cláudia Raquel Ferreira (2021)
Tese de Doutoramento em Ciências da Saúde